Review of the effect of temperature on oil-water relative permeability in porous rocks of oil reservoirs. (1st February 2019) - Esmaeili, Sajjad; Sarma, Hemanta; Harding, Thomas; Maini, Brij
Abstract: Thermal methods of heavy oil recovery involve multiphase flow at high temperatures. Numerical simulation studies of such processes require accounting for changes in the multi-phase flow behavior of the rock-fluid system with increasing temperature. Although the effect of temperature on two-phase relative permeability has been studied for more than five decades, it remains an unresolved issue. Experimental results that frequently contradict each other are still being reported and the issue remains a matter of debate. The purpose of this review is to critically examine the reported results and explore the possible reasons for contradictory results. We have examined the reported results of more frequently cited papers from past five decades and attempted to rationalize the disagreements in findings. There appear to be three main reasons for the lack of consensus in experimentally observed results. The measurements of relative permeability at high temperature are complex and the reported results often include experimental artifacts. Secondly, meaningful relative permeability measurements require that capillary forces control the fluid distribution within the pore space, but this condition is difficult to ensure in viscous oil systems. The third reason is that the impact of temperature is not same in all rock-fluid systems, it depends on how the wettability, interfacial tension and the pore geometry changes with temperature. It becomes apparent that it is not advisable to generalize the effect of temperature on relative permeability from previous studies without having a good understanding of how the underlying parameters that can influence the relative permeability are changing with temperature. The relative permeability of a specific petroleum reservoir may (or may not) vary with temperature.